Implementasi Fungsi Badan Permusyawaratan Desa (BPD) Dalam Mewujudkan Sustainable Development Goals (SDGs) Desa - I Wayan Sutrisna (Jurnal Ilmiah Cakrawarti, 2021)
The paradigm of village development is changing rapidly, so it needs the village government apparatus that can really adjust to the changing situation. The current government is paying very serious attention in efforts to reduce poverty in the village. This is done because with sustainable village development will provide benefits to improve the economy of the community, thereby impacting on improving the welfare of the community. Community participation in the development process is the main key to successful development implementation because it places the community as the driving force or as the subject of development not just as an object. Development with a participatory approach makes the community feel responsible for every process and results of development. The priority of village development has now been directed towards sustainable development goals (SDGs). BPD as a "parliamentary" institution in the village has a strategic position in creating the democratization process as well as being the spearhead of successful development. BPD must maximize its role in realizing participatory development patterns by designing development that is really the will of the community. This paper aims to examine the implementation of the functions of the Village Consultative Agency (BPD) in realizing the Village Sustainable Development Goals (SDGs). This study uses a literacy study approach.